Micro Cough without Cough: A Study on the Vocal Sound Training of Micro Fibrillation of Ngu - Chen, Kaiying (Journal of Literature and Arts Research, 2025)
Micro-coughing, rather than a typical cough, is considered a perfected form of glottal impact. As one of the most significant acoustic theories in vocal music history, it was first introduced by Manuel García, a professional singer. However, due to improper singing techniques, he was forced to quit music at the age of 24. He then dedicated over half a century to research and first proposed the glottal impact theory in 1847. With the invention of the laryngoscope in 1855, the theory was further developed and officially established in 1894. This paper draws on more than 30 years of professional vocal teaching experience to examine the glottal impact theory. It focuses on key issues in muscle energy research, summarizes the main achievements and challenges in this field, and explores specialized research on micro-sound of Ngu aggregation and the expansion of vocal sound training methods. Suggestions and insights from experts are welcome.